2017
DOI: 10.1155/2017/8647917
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Alternative Scenarios for the Cause of Underpressures in the Ordovician Sediments along the Eastern Flank of the Michigan Basin

Abstract: Geoscientific investigations for a proposed deep geologic repository at the Bruce Site, located on the eastern flank of the Michigan Basin, have identified unique and significant underpressured conditions. Along with the measurement of environmental tracer profiles (e.g., helium), this study aims to explore, through a series of numerical simulations, the nature of long-term phenomena responsible for the generation and preservation of formation underpressures. Three families of inverse numerical experiments for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Due to the large capillary pressures in the very fine-grained media in this system, this caused the liquid phase to be significantly underpressured initially. Similar initially underpressured scenarios have been tested by Plampin and Neuzil (2018) and Normani et al (2017). Simulation 29 tests whether pre-existing underpressures could persist through a glacial loading and unloading cycle in a multiphase system.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…Due to the large capillary pressures in the very fine-grained media in this system, this caused the liquid phase to be significantly underpressured initially. Similar initially underpressured scenarios have been tested by Plampin and Neuzil (2018) and Normani et al (2017). Simulation 29 tests whether pre-existing underpressures could persist through a glacial loading and unloading cycle in a multiphase system.…”
Section: Tablementioning
confidence: 99%
“…Permeabilities used in a previous modeling study by Normani et al. (2017) are shown as black lines. The methodology for estimating these parameters is discussed in Section 3.2.…”
Section: Site Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, while multiple lines of evidence suggest the possibility of in situ gas phase methane within the low‐permeability strata at the proposed DGR site (Sterling et al, 2011), the effects of gas phase on hydromechanical processes are still rather uncertain. A recent study (Normani et al, 2017) suggested that the underpressures may have predated glaciation, but this leaves open the question of their cause.…”
Section: Introductionmentioning
confidence: 99%